Deus, erotismo e morte: a santíssima trindade em A obscena senhora D de Hilda Hilst - Dantas, Isabela de Souza (2021)
This research proposes an analysis of the book A obscena senhora D (1982), by Hilda Hilst, a writer from São Paulo, aiming to investigate the way in which dichotomous traits such as life-death, sacred-profane, divine-human and lucidity-madness are reversible, converge between themselves and highlight the enigmatic aspect that surrounds the Hilst literary universe. From the narrative that unveils the protagonist's perceptions of the world, it is also verified how Hillé's experiences build the three main thematic axes identified in the selected fictional corpus – namely, eroticism, death and the idea of God. Thus, to achieve the proposed objective, the work relies on bibliographical research on Hilst fiction as a methodology. At the same time, it is also concerned with the review of specialized literature in relation to the themes analyzed, based on concepts postulated by philosophy and psychoanalysis in consonance with literary theories. The theoretical framework used includes Georges Bataille, Jacques Derrida, Simone de Beauvoir and Shoshana Felman, whose reflections help to explore the issues contained in A obscena senhora D.